Antiseptic spray based on stabilized silver particles: an analysis of antiseptic properties and comprehensive comparison - Manuilov, A; Martynov, A (Annals of Mechnikov’s Institute, 2018)
Introduction. It’s known that some antiseptic sprays based on alcohols can provoke the formation of multi-resistant strains of pathogenic microorganisms. In addition, alcoholic antiseptics has a number of restrictions to use, for example, they can’t to be used in even the presence of micro-trauma on the skin, their ingression into the body and mucous membranes is unacceptable. Alternative can be natural antiseptics based on colloidal silver or silver nanoparticles, as well as silver in ionic form. However, such antiseptics has low efficacy against the most dangerous strains. Company Modern Biochem Technologies Ltd. announced the development of a portable device that generates a natural and safe antiseptic Dew, based on stabilized silver particles. Antiseptic Dew surpasses the vast majority of antiseptics based on silver, and is not inferior in effectiveness to antiseptics based on alcohols. This work is devoted to testing the declared characteristics of Dew and its comparison with antiseptics based on colloidal silver, silver nanoparticles and isopropyl alcohol. Materials and methods. To test the antiseptic effect of these agents, we used four test strains from the American Type Culture Collection: E. Coli ATCC 25922, Staphylococcus Aureus ATCC 25923, Candida Albicans ATCC 885-653 and Proteus Vulgaris ATCC 4636 with billion concentration of colony forming units in 1 ml (108 – 109 CFU/mL, ln CFU/mL = 19.57 ... 20.72). Sowing and screening of cultures were performed on sterile Petri dishes according to the standard procedure. Antiseptic Dew was prepared by prototype provided by Modern Biochem Technologies. The antiseptics of comparison were purchased in Kharkiv, Ukraine. The treatment of contaminated surfaces was performed using mechanical pump sprayers. In accordance with the internal protocol, 1 ml of antiseptic was sprayed from the distance of 10 cm onto the infected surface. To determine the silver content in the Dew, we were used atomic-absorption spectrometer MGA-925MD. Samples for analysis were prepared in accordance with the standard protocol for operation on MGA-925MD. Results & Discussion. For the research we conducted more than 200 microbiological tests. Based on the results of these tests, we can conclude that Dew is indeed superior to other silver-based antiseptics. Also, we can note that in one case, Dew surpassed the effectiveness of the antiseptic based on isopropyl alcohol, but in the second case was slightly less effective. Dew is effective against all four test strains, and the decrease in microbial load after treatment is very substantially - from 109 CFU/mL to 0-101 CFU/mL. The concentration of silver in Dew does not exceed 1.45 ppm and is on average 20 times lower than that of the other tested antiseptics based on silver. Conclusion. Based on the data obtained, we conclude that Dew is a promising antiseptic. Note that the prototype generated the antiseptic with stable characteristics throughout the study. Antiseptics of comparison were shown their effectiveness against test strains, however in one case Dew was surpassed them all in efficiency. In conclusion, we note that we recommend conducting in-depth tests, primarily aimed at determining the effect of Dew in vivo. We also recommend testing Dew on hospital-strains or other resistant strains.